2021
DOI: 10.1128/msystems.00233-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Development of Therapeutics for COVID-19

Abstract: The COVID-19 pandemic is a rapidly evolving crisis. With the worldwide scientific community shifting focus onto the SARS-CoV-2 virus and COVID-19, a large number of possible pharmaceutical approaches for treatment and prevention have been proposed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 339 publications
(501 reference statements)
0
22
0
Order By: Relevance
“…Furthermore, although several drugs that may provide effective treatments for COVID-19 are currently under clinical trial and awaiting approval [12,13], it is currently unclear if daily life around the world will ever return to that of pre-COVID-19 times.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although several drugs that may provide effective treatments for COVID-19 are currently under clinical trial and awaiting approval [12,13], it is currently unclear if daily life around the world will ever return to that of pre-COVID-19 times.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these five groups of keywords showed that during the COVID-19 pandemic, identification of the main viral target proteins and pathogenic mechanisms are important for conducting pharmacological research. Furthermore, drug repurposing and development should be performed to achieve effective viral eradication [25] . In the early phase of the pandemic, prior pharmacological research provided clues for therapeutic schedule exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the surge in research efforts devoted to COVID-19 ( 9 , 10 ), laboratory study of the virus remains a more specialized and time-consuming effort than sequencing. Clinical and epidemiological data are often superficial, measuring only a few variables, other than data sets specific to particular facilities or narrow populations.…”
Section: Perspectivementioning
confidence: 99%